2002
DOI: 10.1021/jf0114381
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Cyclooxygenase Activities of Fatty Acids Found in Food

Abstract: Several commercially available C-8 to C-24 saturated and unsaturated fatty acids (1-29) were assayed for cyclooxygenase-I (COX-I) and cyclooxygenase-II (COX-II) inhibitory and antioxidant activities. Among the saturated fatty acids tested at 60 microg mL(-1), there was an increase in antioxidant activity with increasing chain length from octanoic acid to myristic acid (C-8-C-14) and a decrease thereafter. All unsaturated fatty acids tested at 60 microg mL(-1) showed good antioxidant activity except for undecyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
150
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(165 citation statements)
references
References 12 publications
11
150
1
3
Order By: Relevance
“…that saturated and unsaturated FA, such as myristic, stearic, palmitic, oleic and several oil extracts containing FA, inhibit in vitro both COX and LOX (PaubertBanquet et al, 1997;Yehoshua et al, 1999;Mogul et al, 2000;Henry et al, 2002;Zhang et al, 2002;Gonzalez et al, 2003), which reinforces the validity of the results found here with D-004. Therefore, the inhibition of both LOX and COX activity may explain why the antioxidant activity of D-004 is higher in native than in heatinactivated microsomes, since in this latter condition the LP cellular damage is entirely attributed to non enzymatic mechanisms, and the inhibitory effects of D-004 on both LOX and COX cannot be present to produce a greater overall antioxidant effect.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…that saturated and unsaturated FA, such as myristic, stearic, palmitic, oleic and several oil extracts containing FA, inhibit in vitro both COX and LOX (PaubertBanquet et al, 1997;Yehoshua et al, 1999;Mogul et al, 2000;Henry et al, 2002;Zhang et al, 2002;Gonzalez et al, 2003), which reinforces the validity of the results found here with D-004. Therefore, the inhibition of both LOX and COX activity may explain why the antioxidant activity of D-004 is higher in native than in heatinactivated microsomes, since in this latter condition the LP cellular damage is entirely attributed to non enzymatic mechanisms, and the inhibitory effects of D-004 on both LOX and COX cannot be present to produce a greater overall antioxidant effect.…”
Section: Discussionsupporting
confidence: 82%
“…In line with these facts, it was found that the oral administration of D-003, a mixture of very long chain FA isolated from sugarcane wax, inhibited tissue and lipoprotein LP in experimental models and humans (Castaño et al, 2003). Also, medium and long chain saturated and unsaturated FAs have inhibited in vitro LP (Henry et al, 2002, Zhang et al, 2002 showing oxygen free radical scavenger activity (Chan et al, 1996). Therefore, this study was undertaken to assess whether D-004 displayed in vitro antioxidant effects.…”
Section: Introductionmentioning
confidence: 91%
“…linoleic acid, oleic acid, lauric acid) activities (Henry et al, 2002). Interestingly, the fatty acid compositions of VCOs and CO were comparable to the Codex standards and previous studies (Henry et al, 2002). On the other hand, the difference in antiulcer intensity between the oils could be associated with the way they were processed.…”
Section: Discussionsupporting
confidence: 68%
“…palmitic acid, myristic acid) and anti-inflammatory (i.e. linoleic acid, oleic acid, lauric acid) activities (Henry et al, 2002). Interestingly, the fatty acid compositions of VCOs and CO were comparable to the Codex standards and previous studies (Henry et al, 2002).…”
Section: Discussionsupporting
confidence: 60%
“…Most of the PUFAs have good antioxidant activities [95]. 16 species of seaweeds collected along the Qingdao coastline were screened and evaluated for their antioxidant activities using the β-carotenelinoleate assay system [96].…”
Section: Polyunsaturated Fatty Acids (Pufa)mentioning
confidence: 99%